Felty's syndrome and hypofibrinogenemia: an unusual target for anti-cyclic citrullinated peptide antibodies?. Issue 5 (September 2015) - Lazarou, Ilias; Petitpierre, Nicolas; Auger, Isabelle; Reber, Guido; Roux-Lombard, Pascale; Boehlen, Françoise; Villard, Jean
Abstract Background. Rheumatoid arthritis (RA) is a risk factor for the development of Felty's syndrome and large granular lymphocyte (LGL) leukemia. Anti-cyclic citrullinated peptide (CCP) antibodies are considered highly specific for RA and are directed against various citrullinated antigens, including citrullinated fibrinogen. Anti-CCP antibodies may interfere with the detection of citrullinated proteins and their function. In this article, we describe the possible inhibition of fibrinogen by anti-CCP antibodies with clinical consequences which have never been reported in the literature to our best knowledge. Case report. We present the case of a 79-year-old Caucasian woman with a longstanding history of untreated seropositive RA and who had been investigated for severe neutropenia since several months. The association of splenomegaly led to suspicion of Felty's syndrome. Flux cytometry was compatible with T-cell LGL leukemia. In addition, severe hypofibrinogenemia was detected. The later finding has not been consistently associated with the former clinical entities. Further investigations demonstrated that the anti-CCP antibodies of the patient also recognized the P41 peptide of citrullinated fibrinogen. The patient deceased of intracranial hemorrhage. Conclusion. It is likely, yet not definite, that high anti-citrullinated fibrinogen titers may contribute to low fibrinogen levels and could have contributed to the fatal hemorrhagic event.